Pantangan Menikah Di Hari Peringatan Meninggalnya Orang Tua Di Desa Sarwodadi Kecamatan Comal Kabupaten Pemalang Dalam Perspektif 'Urf - Alfiyani, Kiki (Al-Hukkam: Journal of Islamic Family Law, 2022)
This research is an attempt to find out about the prohibition of marriage on the anniversary of the death of parents in Sarwodadi Village, Comal District, Pemalang Regency which is carried out by the community. Then explain how the background behind the existence of these taboos exists and the concept of taboos from marrying on the anniversary of the death of parents in the perspective of 'urf. This type of legal sociology research (Islam) with a qualitative approach in this case is a legal study whose object is related to legal phenomena. Data collection techniques used are interviews, observation and literature study. Informants in this study were community leaders and the people of Sarwodadi Village. Data analysis used analysis techniques with data reduction, data presentation and drawing conclusions from existing data.The results showed that the taboo on marrying on the anniversary of the death of a person in Sarwodadi Village, Comal District, Pemalang Regency had existed for a long time and lasted from generation to generation. This taboo has become a community custom as a form of respect for parents who have died. If you violate these taboos, it is believed that you will get reinforcements (disaster). In addition, the prohibition of marrying on the anniversary of the death of a parent is included in 'urf saheeh, because it does not conflict with the syara' arguments, does not conflict with mashlahah mu'tabarah and does not bring real mafsadah.”